Putting childhood poverty on the agenda: the relationship between research and policy in Britain 1800-1950 - Platt, L (2003)
The period of 1800 to 1950 saw dramatic changes in the economy and standards of living in Britain, resulting in the development of social policy and the creation of the welfare state. Child welfare became a central concern and, by the end of this period, a rigorously defined and more universal notion of the child and the nature of childhood had emerged. The distinct status of the child was itself partly created through the operation of social policy. Only well into the twentieth century was there a concerted effort to clearly define poverty and to measure and analyse the specific phenomenon of childhood poverty. This paper charts developments in research on childhood poverty and policy responses between 1800 and 1950. It addresses a number of themes including the complexity of the relationship between research and policy; the need for research to be both radical and to relate to its time and place; the relationship between child policy and the delineation of childhood; and linkages between children’s and women’s welfare. The paper argues that compulsory education and restrictions on child labour, while not always directly increasing child well-being, created the conditions under which child welfare research and policy could more fully develop. It shows how national and international child policy has to be informed by systematic research on childhood poverty and how policy-makers persistently reshaped research conclusions, sometimes dramatically, as concern with childhood poverty interacted with other political and economic concerns.